1994
DOI: 10.1038/jcbfm.1994.5
|View full text |Cite
|
Sign up to set email alerts
|

Blood—Brain Barrier Permeability and Brain Concentration of Sodium, Potassium, and Chloride during Focal Ischemia

Abstract: Summary: Brain edema formation during the early stages of focal cerebral ischemia is associated with an increase in both sodium content and blood-brain barrier (BBB) sodium transport. The goals of this study were to deter mine whether chloride is the principal anion that accumu lates in ischemic brain, how the rate of BBB transport of chloride compares with its rate of accumulation, and whether the stimulation seen in BBB sodium transport is also seen with other cations. Focal ischemia was pro duced by occlusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
0
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(68 citation statements)
references
References 33 publications
1
62
0
4
Order By: Relevance
“…Future studies will need to evaluate the effectiveness of administering bumetanide after the onset of cerebral ischemia, as would occur in a clinical setting. A previous study showed that intravenous administration of the Na/H exchange inhibitor dimethylamiloride caused a 20% reduction in edema formation induced by permanent MCAO (Betz et al, 1995), and our own recent studies have shown that intravenous administration of the specific Na/H exchange inhibitor HOE-642 can also reduce edema formation in MCAO (Tran et al, 2004). Thus, a luminal Na/H exchanger may also contribute to edema formation during ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Future studies will need to evaluate the effectiveness of administering bumetanide after the onset of cerebral ischemia, as would occur in a clinical setting. A previous study showed that intravenous administration of the Na/H exchange inhibitor dimethylamiloride caused a 20% reduction in edema formation induced by permanent MCAO (Betz et al, 1995), and our own recent studies have shown that intravenous administration of the specific Na/H exchange inhibitor HOE-642 can also reduce edema formation in MCAO (Tran et al, 2004). Thus, a luminal Na/H exchanger may also contribute to edema formation during ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…As predicted, MCAO caused a decrease in ADC values for the occluded hemisphere (increased edema formation), seen as a decrease in the left/right ADC ratios for all four regions evaluated. Previous studies have shown that permanent MCAO causes a net increase in brain water and a decrease in ADC values, and that the latter provides a very good index of brain swelling (Betz et al, 1994;Rudin et al, 2001). In these studies, we also used gravimetric methods (Menzies et al, 1993) to evaluate the effect of 180 minutes of permanent MCAO on brain water (Table 1).…”
Section: Effect Of Bumetanide On Cerebral Edema In Permanent Middle Amentioning
confidence: 99%
See 1 more Smart Citation
“…Many reports in the literature have studied the increase in the TSC that occurs during acute stroke using small animal models of brain ischemia (2)(3)(4)(5)(6)(7)(8)(9). However, the majority of these studies used invasive direct tissue analysis with flame photometry in which each animal provided data at only a single time point, and therefore, the characterization of TSC over the time course of the stroke in individual animals was not possible.…”
mentioning
confidence: 99%
“…The general consensus from studies in the literature is that the increase in TSC during focal brain ischemia is linear in nature (2)(3)(4)(5)(6)(7)(8)(9)(10). The studies found TSC increases during focal brain ischemia ranging from 16%/h to 35%/h for small animal models (2)(3)(4)(5)(6)(7)(8)(9) and TSC increases ranging from 2.7%/h to 12.7%/h for nonhuman primates (10,11). Because ischemia is associated with time-dependent increases in TSC, noninvasive techniques for the in vivo measurement of the sodium changes in acute stroke are highly desirable.…”
mentioning
confidence: 99%